Pengaruh Store Atmosphere, Kualitas Pelayanan, dan Ragam Produk terhadap Keputusan Pembelian di Restoran Yaw Yaw Surabaya - Reicha Artha Maudia; Agung Pujianto; Ute Chairuz M.Nasution (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The purpose of this study is to determine and analyze the influence of store atmosphere, service quality, and product variety on purchasing decisions at Yaw Yaw Restaurant, Surabaya. This study adopted a quantitative method involving 96 respondents, who were consumers of Yaw Yaw Restaurant in Surabaya and its surroundings. Sampling was carried out using a non-probability sampling technique with a convenience sampling method, where the selected respondents had at least made a purchase once. The collected data was then processed using SPSS software version 25. The results of the analysis showed that store atmosphere has a positive influence on consumer purchasing decisions at Yaw Yaw Restaurant, Surabaya. Likewise, service quality and product variety also positively influence consumer purchasing decisions at Yaw Yaw Restaurant, Surabaya. In this study, the most influential variable is service quality, therefore it is necessary to maintain excellent service quality in a restaurant. High-quality service is directly correlated with increased purchasing decisions based on consumer purchasing experiences. In this study, there is also a variable that has the lowest influence, namely the product variety variable. Yaw Yaw Restaurant, Surabaya needs to review its product variety strategy, ensure that the existing variations are truly relevant and provide added value, while still prioritizing improving the atmosphere and service.